AB0713 Interferon-alpha for the management of lower extremity deep vein thrombosis in behcet's syndrome: a case series. (12th June 2018) - Ozguler, Y.; Hatemi, G.; Cetinkaya, F.; Tascilar, K.; Ugurlu, S.; Seyahi, E.; Yazici, H.; Melikoglu, M.
Abstract : Background: Lower extremity deep vein thrombosis (LEDVT) is a disabling complication of Behçet's syndrome (BS). Relapses are frequent and cause permanent disability due to post-thrombotic syndrome. 1 The management of LEDVT in Behcet's syndrome (BS) constitutes mainly of azathioprine (AZA) and corticosteroids (CS) as first-line agents. 2 Interferon-α (IFN) has been used with good results in the management of eye involvement of BS. However data regarding its efficacy for vascular involvement has been scarse. 3 Objectives: We aimed to evaluate the efficacy and safety of IFN for LEDVT in BS. Methods: All BS pts who had a first episode of acute LEDVT since March 2010 are being prospectively followed with a standard protocol in our dedicated BS centre. Acute LEDVT is confirmed by Doppler ultrasonography (DUS) at initial diagnosis and serial DUS assessment is performed and also repeated in case of clinical suspicion of relapse. Our standard treatment strategy consists of AZA and CSs as first-line treatment in pts with LEDVT. IFN has been used in pts who were refractory or intolerant to this regimen, or who had co-existing eye involvement. Our endpoints for assessing efficacy of IFN have been recanalisation of the index thrombus and prevention of relapses. Presence of recanalisation of thrombosed vein and extension of thrombosis have been assessed at each visit. Recanalisation has been assessed in the transverse plane and defined as the ratio of the vein area at maximum compressibility to the non-compressed vein area. Good recanalisation was defined as a ratio of at least 50%. Adverse events during IFN use were recorded. Results: 33 pts with LEDVT (26 M/7 F) were prospectively followed for a mean of 40.7±13.4 mo. Among these IFN was started in 18/33. In 2 pts IFN was started at the first episode of LEDVT due to co-existing uveitis. Seven pts were treated with IFN due to LEDVT relapses under AZA. In the remaining 9 pts, the reasons for switching from AZA to IFN were adverse events with AZA (n=2), relapse of superficial thrombophlebitis (n=4), leg ulcers due to severe post-thrombotic syndrome (n=2) and eye involvement (n=1). Among 17 pts treated with IFN mainly for vascular involvement during a mean follow-up of 29±20 mo, 3 pts already had good recanalisation when starting IFN. In the remaining 14 pts, 13 (93%) had good recanalisation under IFN. Two pts (11%) experienced relapses. One of the 2 pts who had a relapse had had poor recanalisation despite IFN. In contrast, among the 29 pts treated with AZA, only 13 (45%) had good recanalisation and 13 (45%) pts experienced relapses. Nine fo the 13 pts who had relapses under AZA had poor recanalisation. Overall we observed 23 LEDVT relapses in 15 pts. Relapse rates were 29%, 37% and 45% at 6, 12 and 24 months respectively. The only adverse event with interferon-alpha causing drug withdrawal was thyroiditis in 1 patient. Conclusions: Relapse rate for LEDVT in BS is high despite AZA treatment. IFN seems to be a promising agent for preventing LEDVT relapses and achieving good recanalisation, an important predictor of relapse. The small number of pts and the lack of a parallel control group are the limitations of this prospective study. References: [1] Melikoglu M. Arthritis Rheumatol2014 [2] Alibaz-Oner F. Medicine (Baltimore)2015 [3] Calguneri M.Ann Rheum Dis. 2003 Disclosure of Interest: None declared